ETHOS, LOGOS, PATHOS DALAM PIDATO ANIES BASWEDAN PADA PROGRAM DESAK ANIES EDISI "WARGA MATARAM MENDESAK ANIES BASWEDAN" - Rita Zahara; Anisah Rahmayanti; Athiyyah Nur Roihanah; Hindun (Jurnal Bastra (Bahasa dan Sastra), 2024)
Ethos, Logos, and Pathos are methods of persuasion in rhetoric. These three things can usually be found in someone's speech. In this case, this research analyzes the Ethos, Logos, and Pathos used by Anies Baswedan in the Desak Anies program. The purpose of this analysis is to find out the ethos, logos and pathos contained in Anies Baswedan's speech in the "Desist Anies" edition of the program "Mataram Residents Urge Anies Baswedan". The method used is descriptive qualitative with data collection techniques of listening and taking notes. The results of this research show that in his speech, Anies Baswedan shows rhetorical theory which is related to Aristotle's Artistic Proofs, namely character (ethos), emotion (pathos), and argument (logos), and from these three rhetorical theories Anies Baswedan describes many theories. Rhetoric is emotion (pathos), because Anies Baswedan wants to show his feelings or emotions to the audience.